Changes in muscle strength and physical function in older patients during and after hospitalisation: a prospective repeated-measures cohort study. (9th September 2020) - Hartley, Peter; Romero-Ortuno, Roman; Wellwood, Ian; Deaton, Christi
Abstract: Aim: to investigate changes in knee-extension strength and physical function in older adults during and after acute hospital admission, and the contributions of illness severity, frailty and sedentary activity to changes in knee-extension strength. Methods: prospective repeated-measures cohort study on a sample of participants aged ≥75 recruited within 24 hours of acute hospital admission. Knee-extension, grip strength and functional mobility (de Morton Mobility Index, DEMMI) were measured at recruitment, day 7 (or discharge if earlier), and at follow-up 4–6 weeks later. During the first 7 days, continuous measurement of physical activity and daily measurements of muscle strength were taken. Participants recalled the functional ability they had 2-weeks before admission and self-reported it at follow-up (Barthel Index, BI). Results: sixty-five of 70 participants (median age 84 years) had at least one repeated measure of muscle strength in hospital. Knee-extension strength declined during hospitalisation by 11% ( P < 0.001), but did not change post-hospitalisation ( P = 0.458). Grip strength did not change during hospitalisation ( P = 0.665) or from discharge to follow-up ( P = 0.508). General functional ability (BI) deteriorated between 2 weeks before admission and follow-up ( P < 0.001). Functional mobility (DEMMI) improved during hospitalisation ( P < 0.001), but did not change post-hospitalisation ( P = 0.508). A repeated-measures mixed model showed that greater loss in knee-extension strength during hospitalisation was associated with increased sedentary time, frailty and baseline strength and lower baseline inflammatory levels. Conclusions: our observations add to a growing body of evidence on potential risk factors for hospital-associated deconditioning.